Inside Back Cover: Heterocumulene Sulfinyl Radical OCNSO (Angew. Chem. Int. Ed. 8/2017). Issue 8 (18th January 2017) - Wu, Zhuang; Liu, Qifan; Xu, Jian; Sun, Hailong; Li, Dingqing; Song, Chao; Andrada, Diego M.; Frenking, Gernot; Trabelsi, Tarek; Francisco, Joseph S.; Zeng, Xiaoqing
Abstract : A fleeting exotic heterocumulene radical, OCNSO, is generated in the gas phase at ca. 1200 K, and its conformational ( syn and anti ) interconversion occurs in cryogenic matrices (2.8–15.0 K) upon either irradiation or annealing. As shown by G. Frenking, J. S. Francisco, X. Q. Zeng et al. in their Communication onpage 2140 ff., neutral species formally consisting of two pseudohalogens (OCN and NSO) by sharing the nitrogen atom can be stable enough to be isolated, which enriches the interpseudohalogen family.